The history of diarrhea and stunting in children aged 24-59 months: a relationship study - Rahma Hilmawati, Zaida; Sujiyatini, Sujiyatini; Retnaningsih, Yuliantisari; Maretalinia, Maretalinia (Jurnal Kesehatan Ibu dan Anak, 2024)
The prevalence of stunting in Indonesia remains relatively high. Various consequences can arise due to stunting, including impaired cognitive development in children, suboptimal school performance, and potential long-term impacts on women during adulthood. Diarrhea is identified as one of the triggers for stunting, often caused by insufficient parental supervision and inadequate Exclusive Breastfeeding (EBF) and Complementary Feeding (CF) practices. The study aimed to investigate the relationship between diarrhea occurrence and stunting among toddlers aged 24-59 months. The research employed an observational analysis design using a case-control approach. Sample selection was done through purposive Sampling, involving criteria for inclusion and exclusion. The total sample size was 130 individuals, comprising 65 case samples and 65 control samples. The study was conducted at Dlingo II, Pajangan, and Imogiri II Public Health Centers in Bantul Regency in 2021. Secondary data from registers and medical records were utilized. Data analysis involved the use of the chi-square test and odds ratio (OR). The majority of stunted toddlers were male, had low birth weight, a history of exclusive breastfeeding, and a history of complementary feeding for less than six months. There was a significant relationship between diarrhea and stunting incidence (p=0.023) with an OR value of 3.335 (1.625-6.844). This implies that toddlers with a history of recurrent diarrhea are three times more likely to experience stunting. There is a significant association between diarrhea occurrence and stunting among toddlers aged 24-59 months in the working area of Bantul Regency.